即時反饋系統應用於國小三年級學生修辭教學之行動研究 - 李育懃(Li，Yu-Chin); 歐陽誾(Ou-Yang，Yin) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2015)
Rhetoric is the key to enhance students' listening, speaking, reading and writing abilities. However, both instructors and students deterred from rhetoric easily due to the traditional boring and monotonous teaching methods. By applying the interactive response system, this study aimed to solve the shortcomings of the traditional teaching, and furthermore, to enhance the students’ learning attitude and effectiveness. This study adopted an action research approach. The subjects were 21 third graders in a public elementary school. Teacher’s teaching journals, observation records of peer coaching, students’ interviews, questionnaires, attitude questionnaire and achievement test were collected and analyzed qualitatively and quantitatively. The results of this study include: (1) The implementation of the interactive response system in rhetoric instruction includes the following steps: to select the appropriate rhetoric for students, to design the systematic curriculum, to use the diverse functions of the interacti